1998
DOI: 10.1055/s-1998-4481
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Tertiary α,ω-Diamines via Carbonylative Bis[hydroaminomethylation] of α,ω-Diolefins Using Di(μ-chloro)bis(η4-1,5-cyclooctadine)dirhodium as a Catalyst Precursor

Abstract: Tertiary a,w-diamines are selectively prepared in high yields by the reaction of a,w-diolefins with secondary amines, carbon monoxide and hydrogen in the presence of [Rh(cod)Cl] 2 as a catalyst precursor. This one-pot synthesis proceeds via a hydroformylation-amine condensation-reduction sequence and leads to a mixture of n,n-, n,iso-, and iso,iso-products. One-Pot Synthesis of Tertiary a a, w w-Diamines via Carbonylative Bis[hydroaminomethylation] of a a, w w-Diolefins Using Di(m m-chloro)bis(h h 4 -1,5-cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(21 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…[59] a,w-Diamines with long aliphatic chains separating the two amino functions can also be synthesized by carbonylative bishydroaminomethylation of the corresponding a,w-diole-fins together with suitable amines (Scheme 17). [61] Problems of regioselectivity are circumvented by introducing bulky groups in the vicinity of the double bond. Thus, the two methyl groups of 3,3-dimethylpenta-1,4-diene effect an exclusive formation of the n,n-isomer.…”
Section: Hydroaminomethylationmentioning
confidence: 99%
“…[59] a,w-Diamines with long aliphatic chains separating the two amino functions can also be synthesized by carbonylative bishydroaminomethylation of the corresponding a,w-diole-fins together with suitable amines (Scheme 17). [61] Problems of regioselectivity are circumvented by introducing bulky groups in the vicinity of the double bond. Thus, the two methyl groups of 3,3-dimethylpenta-1,4-diene effect an exclusive formation of the n,n-isomer.…”
Section: Hydroaminomethylationmentioning
confidence: 99%
“…For this transition metal-catalyzed tandem reaction a catalyst based on [Rh(cod)Cl] 2 was employed which showed high activities in reported hydroaminomethylation reactions [33][34][35][36][37][38][39][40]. In Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…Our article provides an overview of general amination reactions using terpenes as starting materials, also including a hydroaminomethylation research overview for other amines than ammonia [24]. The so far described hydroaminomethylations of the natural resource limonene were performed with different amine substrates yielding secondary and tertiary amines [25][26][27]. Rhodium/ phosphine complexes showed very high activities for the product formation.…”
Section: Introductionmentioning
confidence: 99%
“…(ii)B ye mployingasubstrate bearing two reactive sites,at wo-fold hydroaminomethylation is conceivable,i nw hich twon ew independent C À N bonds are formed under the same reaction conditions [reactions (II) and( III), Scheme 2].T his can either be accomplishedb ya pplying ad iolefin or ad iamine in combination with the corresponding stoichiometrica mount of amine or olefin, respectively.W er efer to the term "bis-hydroaminomethylation (bis-HAM)"f or these reactions,i n accordance with Eilbracht et al [27] Only af ew examples can be found in which either of the aforementioned conceptsf or the two-fold HAM have been achieved,a nd no generalp rotocol has been developed so far. [19] In particular, bis-hydroaminomethylations applying ad iaminea nd am onoolefin are especially rare.T able 1s ummarizes bis-hydroaminomethylations in which piperazine( 3), the most frequently used diaminec omponent, was applied.…”
Section: Introductionmentioning
confidence: 82%
“…[25,26] But only in the last two decades,i t became ag eneral tool for the production of various amines (fine chemicals,p harmaceuticals,e tc.) from olefins,p articularly due to the work of Eilbracht, [27][28][29][30][31][32][33] Beller, [23,[34][35][36] and Zhang. [37][38][39][40][41][42] Generally, hydroaminomethylations are,h owever, limited to the aforementioned three auto-tandem catalytic steps and only scattered examples deal with the extensiono ft his sequence.A mong them are combinations of HAM with concurrent esterification of the applied amino acid, [43] formation of the required syngas atmosphere from CO 2 by preliminary reversed water-gas shift (RWGS) reaction [31] andt he access to linear aminesf rom internal alkenes by isomerizing hydroaminomethylation.…”
Section: Introductionmentioning
confidence: 99%